Nursing Care of Children Undergoing Balloon Atrial Septostomy - ละวันนา วีระพล (Journal of The Royal Thai Army Nurses, 2019)
Balloon atrial septostomy (BAS) is an important therapeutic cardiac catheterization and a life-saving interventional procedure for congenital heart disease in newborn or small infant with the purpose of widening a restrictive interatrial communication. It is an emergency intervention in nature, an effective palliative treatment, and allowing the planning for surgery. However, there may have complications during and post intervention phase in the cardiac catheterization laboratory. BAS is going to get better, if there is a multidisciplinary team by co planning. Consequently, nurses have to improve their nursing competency by integrating knowledge related to congenital heart diseases, balloon atrial septostomy, and the complications that may arise in order to monitor patients in reducing the adverse effects of therapeutic cardiac. This would provide nursing care better and holistic care to their families effectively. To provide holistic patient care, nurse must use their experiences and skills by applying the theoretical based during and post intervention phase in practical way.